SolarPrint Hub: school document printing vending machine (SDPVM). - Dumalag, Joshua D. Joves, Louie B. Mendoza, James Noah T. Orduna, Camille L. Rosete, Mark Anthony C. 4 0 16; 5
u
Undergraduate Thesis : (Bachelor of Science in Computer Engineering) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2